WEBLOGS AS A SUBGENRE OF POLITICAL COMMUNICATION / MARKETING - María Jesús Pinar Sanz (Revista de Lingüística y Lenguas Aplicadas)
The aim of this article is to describe the characteristics of weblogs (usually shortened to blog, but occasionally spelled web log), the latest genre of internet communication that has attained widespread popularity (Herring et al. 2005). I will focus my attention on those weblogs which contain any kind of political message during election campaigns. The paper situates blogs with respect to the dominant forms of digital communication and as a powerful tool for developing future election campaigns in light of their low cost and the speed with which news can be published. The generic variables will be studied in detail, taking into account Swales' general theory of genre (1990) and genre theories applied to electronic communication (Yates and Orlikowski, 1992). Register variables (Halliday, 1989; Martin, 2001) will also be thoroughly studied. The results of this study show the characteristics of weblogs with regards to vocabulary, syntactic structures and the use of pronouns among others. The findings are based on an investigation of 20 politically-oriented weblogs, randomly selected during the 2004 American and 2005 British elections.